Associations of GNAS Mutations with Surgical Outcomes in Patients with Growth Hormone-Secreting Pituitary Adenoma - Jung, Hyein; Kim, Kyungwon; Kim, Daham; Moon, Ju Hyung; Kim, Eui Hyun; Kim, Se Hoon; Ku, Cheol Ryong; Lee, Eun Jig (Endocrinology and metabolism (Seoul), 2021)
Background: The guanine nucleotide-binding protein, alpha stimulating (GNAS) gene has been associated with growth hormone (GH)-secreting pituitary adenoma. We investigated the prevalence of GNAS mutations in Korean patients with acromegaly and assessed whether mutation status correlated with biochemical or clinical characteristics.Methods: We studied 126 patients with acromegaly who underwent surgery between 2005 and 2014 at Severance Hospital. We performed GNAS gene analysis and evaluated age, sex, hormone levels, postoperative biochemical remission, and immunohistochemical staining results of the tumor.Results: GNAS mutations were present in 75 patients (59.5%). Patients with and without GNAS mutations showed similar age distribution and Knosp classification. The proportion of female patients was 76.5% and 48.0% in the GNAS-negative and GNAS-mutation groups, respectively (P=0.006). In immunohistochemical staining, the GNAS-mutation group showed higher GH expression in pituitary tumor tissues than the mutation-negative group (98.7% vs. 92.2%, P=0.015). Patients with GNAS mutations had higher preoperative insulin-like growth factor-1 levels (791.3 ng/mL vs. 697.0 ng/mL, P=0.045) and lower immediate postoperative basal (0.9 ng/mL vs. 1.0 ng/mL, P=0.191) and nadir GH levels (0.3 ng/mL vs. 0.6 ng/mL, P=0.012) in oral glucose tolerance tests. Finally, the GNAS-mutation group showed significantly higher surgical remission rates than the mutation-negative group, both at 1 week and 6 months after surgical resection (70.7% vs. 54.9%, P=0.011; 85.3% vs. 82.4%, P=0.007, respectively).Conclusion: GNAS mutations in GH-secreting pituitary tumors are associated with higher preoperative insulin-like growth factor-1 levels and surgical remission rates and lower immediate postoperative nadir GH levels. Thus, GNAS mutation status can predict surgical responsiveness in patients with acromegaly.